Mercedes: a sorghum variety for the production of high-quality forage in Durango, Mexico - Jiménez-Ocampo, Rafael; Rosales-Serna, Rigoberto; Domínguez-Martínez, Pablo Alfredo (Revista Mexicana de Ciencias Agrícolas, 2024)
Agricultural production constantly requires low-priced sorghum seed to reduce costs in forage production. The objective was to develop a sorghum variety adapted to irrigation and rainfed conditions to produce high-quality forage. The Mercedes variety (LAM-1m-2m-3u) was developed by mass selection from a heterogeneous population collected in Las Mercedes, Durango. This variety exceeded the state average yield (32.7 t ha-1), with an average production of fresh forage under irrigation of 42.1 t ha-1. The Mercedes variety, compared to TOM 3, showed fewer days to the emergence of the panicle (81 vs 93 days after sowing: DAS), cut height (256 vs 297 cm), and greater grain weight (17.4 g/1 000 seeds vs 12.8 g/1000 seeds). Mercedes is mainly recommended for producing forage (fresh and silage). The caryopsis is red-orange and shows a long grain surface covered by the glume. Mercedes showed resistance to ergot (Claviceps spp.) and tolerance to lodging. The process of technological transfer of the Mercedes variety is advanced, and the values of yield and quality of forage were corroborated.
Keywords: Sorghum bicolor; adaptability; qualified seed; yield